IMPROVING STUDENTS’ SPEAKING ACHIEVEMENT IN REPORTING PROCEDURE TEXT BY USING VIDEO - Putri Ardilla Lubis and Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study was conducted as an attempt to improve students’ speaking achievement in reporting procedure text by using video. It was a Classroom Action Research (CAR). The subject was students of Grade X, senior high school ( sekolah menengah atas) Budisatrya Medan, which consisted of 35 students. The research was carried out in two cycles and each cycle consisted of three meetings. The instruments used to collect the data were speaking test as quantitative data and Observation sheet, Interview, Questionnaire, and Diary Notes as qualitative data. The results of the speaking tests showed that the students’ score improved in every test. The mean of the students’ score in Orientation test was 51.68, the mean of the students’ score in Cycle I was 65.28, and the mean in cycle II was 81.05. The mean score in cycle II was highest, so it can be said that the students’ speaking achievement improved from 51.68 to 81.05. Based on the Observation Sheet, Interview, Questionnaire, and Diary Notes, it was found that teaching- learning process ran well. The findings of study indicate that using Video significantly improved the students’ speaking achievement. So, English teachers are suggested to use Video in order to improve the students’ speaking achievement in reporting a procedure text.